Thick Electrodes for High Energy Lithium Ion Batteries. Issue 7 (1st April 2015) - Singh, Madhav; Kaiser, Jörg; Hahn, Horst
Abstract : Thicker electrode layers for lithium ion cells have a favorable electrode to current collector ratio per stack volume and provide reduced cell manufacturing costs due to fewer cutting and stapling steps. The aim of this work is to investigate the delivery of energy in such cells compared to cells with thinner electrodes. In this regard, lithium ion cells with single sided 70 μm and 320 μm NMC based cathodes and graphite based anodes with low binder and carbon black contents were prepared and tested in half cell and full cell configurations. Thick and thin electrodes showed capacity losses of only 6% upon cycling at C-rates of C/10 and C/5 while cycling at C/2 resulted in significant losses of 37% for the thick electrodes and only 8% for the thin electrodes. Pouch cells with thick electrodes showed 19% higher volumetric energy density at C/5 in comparison to thinner electrodes. This can be an innovative approach to reduce cell costs and to achieve more competitive prices per energy for applications where only medium to small C-rates are required.